Environmental photochemistry - Boule, P. (Pierre); Bahnemann, D. (Detlef) (Handbook of environmental chemistry. Reactions, processes, 1999)
The authors present the state of the art of photochemical mechanisms and processes of environmental relevance. The volume includes new data e.g. on the sunlight spectrum and latest techniques for the analysis of short-life reactive species. Special chapters deal with biological substances in marine medium and photocatalysis in detoxification processes.